Shopping Tourism Development Through Top Five Products in Yogyakarta City, Indonesia - Wijayanti, Ani; Pramezwary, Amelda; Putri, Emmita Devi Hari; Yulianto, Atun; Nurcahyo, R. Jati; Brahmanto, Erlangga (E-Journal of Tourism, 2021)
Yogyakarta is a city tourism that has no natural tourism potential. Shopping tourism can become an alternative strategy to increase the expenditure and length of tourists stay in Yogyakarta. The research is a qualitative research. The research aims to examine shopping tourism products in Yogyakarta. The research attempts to identify top five products as the main magnetism of shopping tourism in Yogyakarta. Data analysis is conducted through reduction techniques. The research obtained top five culinary products, they are Gudeg, Bakpia, Bakmi Jawa, Kopi Joss, and Kipo, while the top five souvenir products are Batik, Silver, Dagadu, Wayang, and Miniature.